PERAN HADIRNYA KOMUNITAS BAGI MAHASISWA ILMU KOMUNIKASI UNIVERSITAS TRUNOJOYO MADURA DALAM MEMBANTU MENGEMBANGKAN SKILL SESUAI MINAT BAKAT - Fitria Putri Utami; Qoni’ah Nur Wijayanti (JOURNAL SAINS STUDENT RESEARCH, 2024)
Skill is an ability possessed by an individual where this ability will produce value, skills are also needed in the world of work. At the tertiary level, it is a time when a student can freely explore his abilities according to his interests and talents. Every university also definitely has a forum for developing the skills of its students, such as at Trunojoyo Madura University, especially in the Communication Studies Program, which has many communities. This community exists with the aim of helping students support their courses and assist in developing skills that suit their interests and talents. The research carried out by the author aims to find out whether the community attending the Communication Science study program has a role in helping develop students' skills. The sources obtained by the author were observation techniques and interviews with participants.